Analysis Analysis of Enterprise Architecture Design Using TOGAF Framework: A Case Study at Archival Unit of Faculty of Agricultural Technology of Udayana University - Ariawan, Pasek Agus; Putra, Indra Sukadiana; Sudarma, I Made (International Journal of Engineering and Emerging Technology; Vol 2 No 2 (2017): July - December, 2018)
Abstract — The research aims to analyze the enterprise architecture design of the archival unit of the Faculty of Agricultural Technology of Udayana University. The method used in developing the enterprise architecture is TOGAF framework. The TOGAF framework includes the preliminary stage, architectural visions, business architecture, information system architecture, technology architecture, opportunities and solutions, migration planning, implementation governance and change management architecture. This paper only covers discussion up to the planning stage of migration. The research revealed that enterprise information systems can create an integrated information system. TOGAF ADM can generate an enterprise architecture design that will be applied in the archival unit of the Faculty of Agricultural Technology of Udayana University, and able to meet the needs of business processes and users of the archival unit of the said faculty. TOGAF ADM can produce an IT blueprint of the archival unit of the said faculty. Keywords — Archive, TOGAF, Enterprise Architecture